1999
DOI: 10.1002/(sici)1521-3765(19990604)5:6<1828::aid-chem1828>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Grid and Helical Hydrogen-Bonded Arrays Incorporating Bowl-Shaped Receptor Sites That Bind Globular Molecules

Abstract: 1,2-Dicarbadodecaborane(12) (o-carborane) and bowl-shaped cyclotriveratrylene (CTV) self-assemble through bifurcated C ± H carborane´´´( O) 2 hydrogen bonds into infinite arrays with two-dimensional (2D) hexagonal grid or helical chain topologies. The in-built shape-specific receptor sites bind o-carborane or fullerene C 70 . The structures of two such supramolecular systems in the solid state were established: (ocarborane) 2 (CTV) features hydrogenbonded carborane´´´CTV hexagonal grids as well as CTV´´´carbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 7 publications
2
72
0
Order By: Relevance
“…The transition from simple hostguest assembly with discrete domains [6] to coordination polymer [7] is made by …”
Section: Coordination Polymers As Hosts For Carboranesmentioning
confidence: 99%
“…The transition from simple hostguest assembly with discrete domains [6] to coordination polymer [7] is made by …”
Section: Coordination Polymers As Hosts For Carboranesmentioning
confidence: 99%
“…For example, CTV molecules form stacked columns, and further packing of these columns results in the formation of a channel structure capable of guest accommodation. 31,32 Moreover, Raston and Hardie have found that CTV can also form network crystal structures mediated by hydrogen bonding with o-carborane 33 or by complexation with alkali cations 34 at their veratrole parts. In the structures of coordination polymers, the cavity of cyclotriveratrylene serves as recognition sites for several spherical anions such as halogenated carbaborane anions 35 is not encapsulated in the cavity of CTV directly but sandwiched by two CTV molecules to form a loose capsule-like structure, and the disordered CH 3 CN molecules are placed in the cavity of CTV.…”
Section: Cyclotriveratrylenementioning
confidence: 99%
“…The cup-shaped cyclotriveratrylene derivatives (CTV) are among the key structures that have been exploited for many years for the design of molecular hosts [1][2][3][4][5][6][7]. They are interesting starting compounds for the construction of new macromolecular architectures such as solid inclusion complexes [8], biosensors, bis-cryptophanes to study the guest…”
Section: Introductionmentioning
confidence: 99%